Traffic Congestion in Ecuador: A Comprehensive Review, Key Factors, Impact, and Solutions of Smart Cities - Luis Roberto Jacome Galarza; Wilson Eduardo Jaramillo Sangurima; Silvia Alexandra Jaramillo Luzuriaga (Latin-American Journal of Computing)
This study explores the main sources of traffic congestion in Ecuadorian cities and propose solutions to address this issue. The findings reveal that the main causes are natural disasters disrupting the transportation infrastructure and leading to chaotic traffic flow, lack of infrastructure maintenance, inadequate education, cultural issues, improper traffic signal timing, or the absence of exclusive lanes for public transportation. Fast transit projects have also faced obstacles, including a lack of political leadership, underestimation of implementation complexities, rushed planning processes, resistance from stakeholders like bus operators, and inaccurate cost estimations. Vehicle pollution is another consequence of lower-quality fuel and the topography of highland cities, which demand more engine power. The proposed solutions are categorized into three types: smart city technologies, implementing regulations, and enhancing public transportation systems. To address traffic accidents, it is recommended to identify high-risk areas, monitor fleet variables of buses, educate the population on responsible driving practices, and implement designated driver applications. By considering and implementing these solutions, Ecuadorian cities can alleviate traffic congestion, enhance transportation efficiency, reduce pollution, and improve road safety.